ISLAM NUSANTARA: A STUDY ON THE EFFECT OF LOCAL WISDOM VALUE ON CUSTOMARY COMMUNITY’S PIETY IN KAMPUNG NAGA - Azis Muslim (Institut Agama Islam Negeri (IAIN) Surakarta, 2021)
Community empowerment takes a long time and an appropriate strategy to achieve success. Moreover, innovation delivered constitutes the regulations restricting the empowered community’s moving space. This research generally portraits pamali (taboo) strategy in conducting community empowerment and particularly aims to study local wisdom value in building the piety of Kampung Naga community. The research was conducted using phenomenological descriptive qualitative approach with an interactive technique of analysis. Data collection was carried out through interview, observation, and documentation. The result of research showed that innovation constituting local wisdom made by Kampung Naga community’s ancestor could build piety in three domains: spiritual, social, and environment. Through those three pieties, Kampung Naga community becomes a powerful Islam community in archipelago nuance and becomes Islam community that is rahmatan lil alamin.